Sistem Pengendali Energi Listrik Menggunakan Raspberry Pi Pada Smart Building Kampus - Masnur, Masnur; Marlina, Marlina (Building of Informatics, Technology and Science (BITS), 2022)
Electrical energy is a very important need that must be met for human needs, but the source of the power plant sometimes uses non-renewable natural resources. Savings in the use of electricity has an impact on the preservation of nature and the cost of electricity used. The problem is the waste of electricity use and the negligence of its users, such as not turning off electrical equipment or forgetting to leave the room. So "Electrical Energy Control System Using Raspberry Pi in Smart Building at Muhammadiyah University of Parepare was made". The method used is to make a prototype that is capable and can be controlled remotely using the internet, this system can be controlled either using a PC or using a mobile phone. The system uses the IP Address contained in the raspberry pi, by accessing the IP address the user can control the system so that the user does not need to be too anxious when leaving the room, because the user can monitor the temperature and see pictures of the room when left. By using this system, users can control electrical equipment, can monitor room temperature when left to leave, can ON/OFF the lights and air conditioning in the room, monitor the movement of human objects which are then synchronized with the ON/OFF lights. The system is also capable of recording the room which is then saved in jpg format